2018
DOI: 10.30773/pi.2017.04.24
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean version of the 16-Item Prodromal Questionnaire in a Non-Help-Seeking College Population

Abstract: Objective To examine the reliability and validity of the Korean version of the 16-item Prodromal Questionnaire (KPQ-16) in non-help-seeking university students. Methods Among 2,246 university students participated in the initial screening, 257 subjects with KPQ-16 scores ≥4 were interviewed. The criteria for ultra-high risk (UHR) of psychosis of the Comprehensive Assessment of At-Risk Mental States (CAARMS) were the gold standard for diagnosis. An exploratory modified version of the questionnaire (mKPQ-16), to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…In this study, the PPV of the CAPE-15 distress score was improved (32.4%) compared with previous screening tools, 6,7,10 but it was still relatively low for a screening tool with strong predictive power. Nevertheless, when a tool is used to screen for a serious, low-prevalence disease, such as psychosis, the chosen cutoff point should provide good sensitivity, even when the PPV is low or the false-positive rate is high.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…In this study, the PPV of the CAPE-15 distress score was improved (32.4%) compared with previous screening tools, 6,7,10 but it was still relatively low for a screening tool with strong predictive power. Nevertheless, when a tool is used to screen for a serious, low-prevalence disease, such as psychosis, the chosen cutoff point should provide good sensitivity, even when the PPV is low or the false-positive rate is high.…”
Section: Discussionmentioning
confidence: 48%
“…In this study, the cutoff score of the mKPQ-16 for identifying psychosis risk was the same and its PPV was similar to those of our previous validation study for the mKPQ-16. 7 This suggests that the process used in the current study was credible and showed the stability of the mKPQ-16 as a screening tool. The sensitivities and specificities of the PQ-16, PQ-B, and ESI were below 80% in previous studies, 6,7,10 but those of the CAPE-15 in this study were 91.7% and 85.2%, respectively.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations